(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2023)
Accompany elementary school children in learning is crucial because first-graders experience transition from preschool to primary school. During the transition period, parents might face challenges as they need to divide their time to work and accompany their children’s learning. This might result in stress as the changes or the demands of work and daily life can cause disruptions and thoughts. The preliminary study revealed that 80% of parents often have trouble relaxing, get irritated easily, spend so much energy worrying, get angry easily, find it hard to be patient, and get easily agitated. Research Objective to find out the correlation of work with stress levels of parent in accompany children’s learning at SD Negeri Sempu and SD Negeri Pokoh . This study was non-experimental quantitative research applied an analytical observational method with a cross-sectional design. A total sampling technique was used to obtain samples from 56 people. The research instruments were the DASS-42 questionnaire and closed questions relating to job classification. The bivariate analysis used the Theta Test. The results showed that parents who accompany their children’s learning at SD Negeri Sempu and SD Negeri Pokoh 1 were mostly female, and they were helped by their mothers. Most of them were housewives and experienced mild stress. The result of the Theta test at SD Negeri Sempu was 0.037 and at SD Negeri Pokoh 1 was 0.041. There was a very weak correlation of work with stress levels of parent in accompany children’s learning at SD Negeri Sempu and SD Negeri Pokoh 1.